CYBERSECURITY AS A MAJOR FACTOR IN CHINA’S NATIONAL SECURITY - Azimova, Guli Nodirbek qizi (Educational Research in Universal Sciences, 2023)
Over the past two decades, the People’s Republic of China has paid special attention to ensuring the information security of the state and society. The rapid development of information technology has added a new aspect to the national security system of the People’s Republic of China - cybersecurity.